Mapping a lateralization gradient within the ventral stream for auditory speech perception - Specht, Karsten (Frontiers in Human Neuroscience, 2013)
Recent models on speech perception propose a dual stream processing network, with a dorsal stream, extending from the posterior temporal lobe of the left hemisphere through inferior parietal areas into the left inferior frontal gyrus, and a ventral stream that is assumed to originate in the primary auditory cortex in the upper posterior part of the temporal lobe and to extend towards the anterior part of the temporal lobe, where it may connect to the ventral part of the inferior frontal gyrus. This article describes and reviews the results from a series of complementary functional magnetic imaging (fMRI) studies that aimed to trace the hierarchical processing network for speech comprehension within the left and right hemisphere with a particular focus on the temporal lobe and the ventral stream. As hypothesised, the results demonstrate a bilateral involvement of the temporal lobes in the processing of speech signals. However, an increasing leftward asymmetry was detected from auditory-phonetic to lexico-semantic processing and along the posterior-anterior axis, thus forming a “lateralisation” gradient. This increasing leftward lateralisation was particularly evident for the left superior temporal sulcus (STS) and more anterior parts of the temporal lobe.